AHMADIYYA AND PEACEFUL-COEXISTENCE; GROUNDING TOLERANCE IN THE MIDDLE OF MINORITY GROUP - Ali Ilham Almujaddidy (UIN Sunan Kalijaga Yogyakarta, 2017)
Ahmadiyya came into the world on a mission of peace and renewal through the values of morality teachings. In the context of Indonesia, Ahmadis have been coming to the archipelago through the youth of Sumatra since 1924 and has received positive responses as a new religious movement at that time. But in its development, the phenomenon of Ahmadiyya emerged as an issue of protracted conflicts and endless until today. Some of the group that is the true Islam with shouts of Allahu Akbar carried out the attack against Ahmadiyya in Indonesia, including Ahmadiyya in Manis Lor, Kuningan.